2004
DOI: 10.1002/ijc.20273
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Hodgkin's lymphoma among asthmatics exposed to pesticides

Abstract: We conducted a pooled analysis of population-based casecontrol studies in Iowa, Minnesota and Nebraska to investigate whether asthma modifies risk of non-Hodgkin's lymphoma (NHL) associated with pesticide exposures. Cases (n ‫؍‬ 872) diagnosed with NHL from 1980 to 1986 and frequency-matched controls (n ‫؍‬ 2,381) randomly selected from the same geographic areas as the cases were included. Information on use of pesticides and history of asthma was based on interviews. Unconditional logistic regression was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 30 publications
2
36
2
Order By: Relevance
“…Immunotoxicity, enzyme induction, dioxin-like effects and endocrine disrupting effects might be relevant in this regard. An interaction with viruses, such as the Epstein-Barr virus,5 7 or allergic diseases, such as asthma,33 has been suggested, but uncertainties persist as negative findings have also been published 6 12…”
Section: Discussionmentioning
confidence: 99%
“…Immunotoxicity, enzyme induction, dioxin-like effects and endocrine disrupting effects might be relevant in this regard. An interaction with viruses, such as the Epstein-Barr virus,5 7 or allergic diseases, such as asthma,33 has been suggested, but uncertainties persist as negative findings have also been published 6 12…”
Section: Discussionmentioning
confidence: 99%
“…Organophosphates have been associated with leukemia and other immunologically related cancers in the epidemiologic literature (Brown et al 1990; Cantor et al 1992; Clavel et al 1996; De Roos et al 2003; Lee et al 2004; Waddell et al 2001; Zahm et al 1993). The leukemogenic effects of organophosphates may be related to immune function perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…Later, to evaluate specific pesticides as risk factors for NHL, Waddell et al (2001) and De Roos et al (2003) pooled three population-based case–control studies conducted in the midwestern United States and found odds ratios (ORs) for fonofos exposure of 1.7 [95% confidence interval (CI), 1.1–2.6] and 1.8 (95% CI, 0.9–3.5), respectively. Further, because NHL is associated with a compromised immune system, Lee et al (2004) pooled two of the studies to evaluate risk from pesticide exposure and asthma, a marker of immune alteration, and observed an elevated main effect for fonofos use (OR = 1.6; 95% CI, 1.0–2.4) as well as an elevated joint effect of fonofos use and asthma (OR = 3.7; 95% CI, 1.3–10.9).…”
mentioning
confidence: 99%
“…44 A significantly increased risk of extranodal NHL was reported for malathion (OR 5 3.52, 95% CI: 1.24-10.0), however. 44 Lee et al 51 reported non-significantly increased relative risks of NHL in association with several individual pesticide exposures among asthmatics compared to non-asthmatics.…”
Section: Occupational and Environmental Factors Occupational And Envimentioning
confidence: 99%